Integrating User Experience (UX) model with planning game practice in extreme programming - Mahmod, Musyrifah (Universiti Utara Malaysia, 2007)
In recent years web application is becoming more complex and mission critical where it implements continual integration of new requirements for business logic.Almost all the web system developed demand faster time-to-market for competitive advantage.Such demands have increased the reputation of agile software processes such as Extreme Programming (XP) that allow flexibility and yet let the teams increase development productivity while maintaining software quality.However, XP too has its own strength and weakness such as one of XP principle that focuses on very minimal documentation and communicating the requirement for web application development between the customer and the developers.Even though through literature, there are successful projects that adopted XP, but if one approach is successful on one project does not mean the same approach will get the same results if applied on different projects.This research aims to propose an integration of User Experience (UX) model in Planning Game practice in XP to facilitate better requirements analysis for web application development.This research will only focus on functional requirements for web application development.